Primary rhinosporidiosis of parotid duct (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Rhinosporidiosis is a chronic granulomatous disease. It is commonly seen in Southern Asia specially in India, Bangladesh, Nepal and Sri Lanka and mainly involves the mucosa of the nasal cavity.Case report: We report here an unique case of parotid duct rhinosporidiosis which was incidentally diagnosed by histopathological examination in a 26-year-old male. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12021 Bangladesh J Otorhinolaryngol 2012; 18(2): 212-214